2008
DOI: 10.4141/cjas07086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplements of folic acid on reproductive performance in ewes

Abstract: . W. 2008. Effects of dietary supplements of folic acid on reproductive performance in ewes. Can. J. Anim. Sci. 88: 489Á497. The objective of this project was to assess the impact of periconceptional folic acid supplementation on the reproductive performance of prolific and non-prolific ewes, in the estrous and anestrous seasons. Two initial trials took place during the estrous season at two experimental sites where 38 Dorset and 39 half-Finn half-Dorset ewes (site A) as well as 80 Dorset ewes (site C) were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Women who take folic acid supplements have lower homocysteine concentrations in their follicular fluid, oocytes with better quality, and a high degree of mature oocytes [ 72 ]. It has been reported that the folate concentration in prolific breeds ewes is higher than from non-prolific breeds [ 73 ], but a more recent study reported that folic acid supplementation to prolific and nonprolific ewes increase folate concentration in red cells and plasma but hasn’t any effect on fertility or litter size [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women who take folic acid supplements have lower homocysteine concentrations in their follicular fluid, oocytes with better quality, and a high degree of mature oocytes [ 72 ]. It has been reported that the folate concentration in prolific breeds ewes is higher than from non-prolific breeds [ 73 ], but a more recent study reported that folic acid supplementation to prolific and nonprolific ewes increase folate concentration in red cells and plasma but hasn’t any effect on fertility or litter size [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Folic acid deficiency in female mammals during the preconception and gestational periods can impair fertility, folliculogenesis, and early embryogenesis (Laanpere et al, 2010). In a study in which dietary folic acid was given to ewes around mating, the ovulation rate increased during the estrous season for the prolific breed receiving the supplement compared with prolific control ewes and ewes of a nonprolific breed (Méthot et al, 2008). Supplementary folic acid administered to sows before and during gestation significantly increased the number of piglets born and the number of piglets born alive (Matte et al, 1984) by decreasing the number of dead fetuses at 30 d of gestation .…”
Section: Reproductionmentioning
confidence: 99%
“…Jika terjadi penurunan nilai RBC dan HGB pada induk bunting perlakuan disebabkan karena pada saat bunting, induk sapi sangat memerlukan nutrisi untuk pertumbuhan fetus. Pemberian vitamin B-kompleks saat ternak bunting sangat dibutuhkan untuk perkembangan fetus, karena vitamin ini merupakan vitamin yang dapat meningkatkan perkembangan fetus terutama vitamin B6, vitamin B9 dan vitamin B-12 (Me´thot et al 2008;Mitchell et al 2014) sementara itu pada kajian ini digunakan vitamin B-kompleks yang hanya mengandung vitamin B1, B2 dan B6. Di sisi lain pakan yang diberikan peternak pada induk sapi perlakuan adalah pakan standar yang didominasi rumput alam, sekali waktu diberi rumput gajah atau biomas jagung tanpa pemberian mineral dan suplemen lainnya.…”
Section: Gambar 1 Grafik Efektivitas Vitamin B-kompleks Pada Induk Sunclassified